Intimate partner violence help-seeking attitudes in the Democratic Republic of the Congo: a population-based analysis - Shannon N. Wood; Anaise Williams; Pierre Z. Akilimali; Dynah Kayembe; Suzanne O. Bell; Michele R. Decker (BMC Public Health, 2025)
Abstract Background Intimate partner violence (IPV) is the leading form of gender-based violence globally, and is particularly pronounced in the Democratic Republic of the Congo (DRC), where 36% of women report experiencing physical and/or sexual IPV within the past 12 months. Despite increased attention to IPV service provision, help-seeking remains suboptimal. In DRC provinces of Kongo Central and Kinshasa, we examined: 1) characteristics of IPV and related help-seeking, 2) women’s attitudes towards IPV help-seeking, and 3) the association between IPV help-seeking attitudes and help-seeking. Methods A population-based reproductive health survey conducted in Kongo Central and Kinshasa provinces of the DRC from December 2021-February 2022 examined past-year IPV and related help-seeking among partnered women participating in a gender-based violence module (n = 707 Kinshasa; n = 692 Kongo Central). Descriptive analyses examined forms of IPV (physical, sexual, emotional), help-seeking (informal/formal sources), and help-seeking attitudes. Among women who experienced IPV, bivariate and multivariable logistic regression examined individual help-seeking attitudes on help-seeking experience. Results Approximately one in three women reported past-year IPV (35.3% in Kinshasa, 29.7% in Kongo Central). Among past-year IPV survivors, 73.1% in Kinshasa and 62.3% in Kongo Central sought no help; for women who did seek help, less than 2% were from formal sources. Attitudes around women seeking help from police and women’s groups were largely negative (i.e., women did not feel these sources could help). Disagreeing or strongly disagreeing with attitude “a woman who seeks help from the police for domestic violence shames her family” was associated with increased odds of help-seeking in multivariable pooled models (aOR:1.73; 95% CI: 1.03, 2.89; p < 0.05). Conclusions These findings reiterate the need to dismantle harmful gender systems and promote survivor-centered services. Confidence in services and corresponding attitudes favorable of seeking help are necessary to promote help-seeking for this leading form of gender-based violence.